ANALISIS PENGARUH INKLUSI KEUANGAN MELALUI LAYANAN FINTECH P2P LENDING TERHADAP HUMAN DEVELOPMENT INDEX INDONESIA - Muharni, Riska Dwi; S. S, Vietha Devia (Contemporary Studies in Economic, Finance and Banking, 2022)
Financial inclusion is closely related to a system that ensures the accessibility, availability and use of the formal financial system for all economic actors. Through the use of fintech, it can accelerate the expansion of public access to financial services so as to increase financial inclusion. Increasing financial inclusion is expected to have an effect on increasing the Human Development Index. This study aims to determine how the effect of financial inclusion through fintech services specifically for p2p lending services on the Human Development Index in Indonesia, using access indicators, availability indicators, and usability indicators as the independent variable and the Human Development Index as the dependent variable. This research is a type of quantitative research using multiple linear regression analysis that uses secondary data, in the form of statistical report data on Indonesian fintech and the human development index starting from January 2019 to December 2021. The results of the analysis show that partially the indicators of access, availability and usability have an effect on significant to the Human Development Index in Indonesia. Simultaneously, all indicators of financial inclusion through fintech p2p lending services have a significant effect on the Human Development Index in Indonesia.